Análise das cardiopatias congênitas de urgência em São Paulo - a rede CROSS - Oliveira, Maira Marasca de (2022)
The presence of waiting lists, even for urgent surgical procedures, is a major challenge for a Universal Health System. Added to this, the importance of infant mortality as an indicator of population health and the need to reduce the early neonatal component, represented in large part by cardiac malformations. This study analyzes for the first time data from the Central de Regulação do Estado de São Paulo, of 1,437 children with urgente surgical congenital heart disease and less than one year of age, from February 2019 to February 2021, registered in the system due to need to perform pediatric cardiac surgery in specialized centers. The objective of the study is to identify factors related to access, with the scope of creating new health policies. This is a descriptive study with a quantitative and qualitative approach, simultaneous. A quantitative methodology was used to assess the independent variables: sex, place of origin, referral hospital, main diagnosis of congenital heart disease, other diagnoses, presence or absence of a court injunction and classification on the RACHS surgical risk adjustment scale. The dependent variable was the child's transfer time, from registration in the CROSS system to completion. The relationship between the variables was studied, in addition to the comparison of transferred and non-transferred groups, pre-pandemic and during the pandemic. The qualitative methodology was carried out through thematic categorization of the interviews with the network's regulatory physicians. The results of the study showed that 30% of these children are not transferred, with this group having a higher frequency of more complex surgeries (RACHS 4 to 6), and that pathologies such as pulmonary atresia and hypoplastic heart syndrome have a longer transfer time or a higher prevalence in the untransferred group. It also showed that the transfer time was shorter during the pandemic period, due to the optimization of emergency surgeries to the detriment of elective ones. He also highlighted the participation of the private sector as a way to make the public system operational and the need to encourage and expand existing policies, such as the Coraçãozinho test. The interviews with the network's regulatory physicians demonstrated the importance of teleconsulting and telemedicine instruments, the impossibility of early fetal diagnosis as an alternative, given the current low supply of beds; and the interference of the court injunction in a negative way, making it difficult to choose the really priority patient. The research suggested new health policies, such as: prioritizing pathologies on the waiting list, training existing centers and incentive to finance highly complex surgeries, implementing teleconsulting and telemedicine instruments, expanding new management alternatives and expanding health care policies of diagnosis already in force.